Perencanaan Anggaran Kas yang Efektif Dala Menjaga Likuiditas dan Meningkatkan Rentabilitas Larispa Indonesia - Yolla Sarah Ananda Harahap; Murni Dahlena Nasution (Forum Kerjasama Pendidikan Tinggi, 2022)
The purpose of this research is to find out and analyze the appropriateness of the preparation of the company's cash budget and to find out and analyze whether the role of the cash budget supports the effectiveness of the company's cash management. The type of research used in this research is a case study with a descriptive method. Calculations are based on liquidity ratios, activity ratios, and profitability. This shows that financial preparation has increased with liquidity, activity and profitability ratios, which means that financial management is running well and the impact is better than before. The company's liquidity and profitability grow significantly every year. It can be concluded that the cash budget of the Larispa company for the 2019-2021 period was able to maintain liquidity and increase profitability in accordance with the smooth operation and survival of the company thanks to an increase in operating profit and sales.